Kemampuan Pt Bumi Resource Tbk Dalam Membayar Seluruh Hutangnya Pada Periode Tahun 2022-2023: Analisis Rasio Solvabilitas - Fadhilah, Khaerunnisa; Dewi, Galuh Kirana; Gultom, Jona Amsal; Ferdianty, Fera; Putra, Angga Sanita (Jurnal Ilmiah Wahana Pendidikan, 2025)
The solvency ratio analysis in this study is used to evaluate the ability of PT Bumi Resources Tbk to meet its financial obligations during the 2022/2023 period. The performance of mining companies, including PT Bumi Resources, has been affected by the impact of the Russia-Ukraine war on the global energy market, which includes supply disruptions and commodity price fluctuations. This study was conducted using quantitative and descriptive methods, with data collected through document study techniques. The analysis results show changes in the company's solvency ratios; the Debt to Asset Ratio was recorded at 37.20% in 2022 but decreased to 33.98% in 2023. The Debt to Equity Ratio also declined from 59.23% to 51.46%. This study is expected to provide a comprehensive overview of the company's financial performance and debt management trends.